An Exploratory Study of Number of Children Desired and What Accomplished in Family Settings - A.O. Adejumo; S.A. Taiwo; O. Job; O.L. Adeniyi; P.E. Oguntunde; O.A. Odetunmibi; A.A. Akinrefon (University of Sofia, 2017)
In any family settings, racing children is a big decision that requires serious self-reflecting and communication between couples. In African settings, there is usually a rift in the agreement of the number and the gender of children to be borne by couples; while the man prefers a male child, the wife may prefer a female child instead. The number of children by the couple also determine the kinds of education those children will eventually have later. To this effect, in this research work, we want to study the Man's proposed and actual number of children; the degree of association in the man's decision using Quasi symmetry and Homogeneous Agreement model; how well some factors (Age, Religion, Family status, Occupation, Level of education and Ethnic group) influence the number of children; and to know the stopping rule for child bearing by the man. It was observed that 16.2% of the respondents had above the number of children proposed when they stopped bearing children, 21.5% of the respondents had below the number of children proposed when they stopped while 62.3% of the respondents had the exact number of children proposed when they eventually stopped bearing children. We observed that Age and Religion influence the number of children. We also observed that the probability of having at least one male child is 0.8019 based on the available data. The chance of any newly wedded couple ever having a male child at any trial follows a geometric distribution . Quasi symmetry model has a better fit for agreement measure than Homogeneous agreement model.